2011
DOI: 10.1093/nar/gkr695
|View full text |Cite
|
Sign up to set email alerts
|

Generating the optimal mRNA for therapy: HPLC purification eliminates immune activation and improves translation of nucleoside-modified, protein-encoding mRNA

Abstract: In vitro-transcribed mRNA has great therapeutic potential to transiently express the encoded protein without the adverse effects of viral and DNA-based constructs. Mammalian cells, however, contain RNA sensors of the innate immune system that must be considered in the generation of therapeutic RNA. Incorporation of modified nucleosides both reduces innate immune activation and increases translation of mRNA, but residual induction of type I interferons (IFNs) and proinflammatory cytokines remains. We identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
678
6
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(755 citation statements)
references
References 32 publications
(49 reference statements)
18
678
6
11
Order By: Relevance
“…Apoptosis in untransfected and transfected cells was indistinguishable. Our observations are consistent with previous reports using many different cell types and mRNA packaging systems (35,36). To minimize the loss of cell viability, the delivery system may need to be modified to reduce epithelial cytotoxicity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Apoptosis in untransfected and transfected cells was indistinguishable. Our observations are consistent with previous reports using many different cell types and mRNA packaging systems (35,36). To minimize the loss of cell viability, the delivery system may need to be modified to reduce epithelial cytotoxicity.…”
Section: Discussionsupporting
confidence: 91%
“…Use of this approach for therapeutic purposes in mucosal infections would be enhanced with an mRNA packaging system that would target epithelial cells more specifically and increase mRNA stability and minimize immune activation, as suggested by Weissman and colleagues (35). Ultimately, the test for mRNA transfection efficiency is a new or augmented function and minimal associated cytotoxicity or induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, purification of the IVT mRNA can further mitigate the immune stimulatory properties as was demonstrated by Kariko et al by the removal of dsRNA contaminants through highperformance liquid chromatography purification [91].…”
Section: Modifying the Mrnamentioning
confidence: 98%
“…Early studies by Kariko and Weissman first used chemically modified mRNA as a tool to express proteins of interest in target cells in vitro (Kariko et al 2005(Kariko et al , 2011. Any unmodified mRNAs, including mRNA, that enter the cells via the cell membrane are recognized by the innate immunity (Weissman et al 2000;Ni et al 2002;Kariko et al 2004).…”
Section: Synthetic Chemically Modified Mrna As a Tool For Protein Exmentioning
confidence: 99%
“…2) (Kariko et al 2005). However, by modifying the nucleotides in the in vitro transcription system, initially substituting pseudouridine for uridine and 5-methyl-cytosine for cytosine (Kariko et al 2005(Kariko et al , 2011, it was found that change in one or two modified nucleotides leads to a change in the secondary structure of the mRNA that allow modified mRNA to escape detection by the innate immunity response of the host cell, and still allow the translational machinery to efficiently express a given protein of interest in living cells in vitro (Kariko et al 2005(Kariko et al , 2011. This approach primarily has been used in in vitro transfection model systems, including reprogramming strategies to express the four reprogramming proteins, resulting in efficient generation of induced pluripotent stem (iPS) cells from a variety of somatic cell types (Warren et al 2010).…”
Section: Synthetic Chemically Modified Mrna As a Tool For Protein Exmentioning
confidence: 99%